Identification of RAPD Markers and Development of SCAR Markers Linked to a Powdery Mildew Resistance Gene, and their Location on Chromosome in Wheat Cultivar Brock - Zhenying Wang; Pei Zhao; Hong Chen; Youngkang Peng; Chaojie Xie; Qixin Sun; Zuomin Yang (Plant Production Science, 2005)
Wheat cultivar Jing 411 which is susceptible to powdery mildew, and wheat cultivar Brock and NILs of Jing 411, which are resistant to powdery mildew were analysized for polymophisms using 213 random amplified polymorphic DNA primers. Only one primer (S2092) stably produced a polymorphic band between the resistant and susceptible plants. Linkage analysis of this marker (S2092972) revealed that the polymorphism existed in a 131 F2 segregating population. S2092972 was closely linked to a powdery mildew resistance gene in wheat cultivar Brock, at a linkage distance was 4.9 cM. S2092972 was converted to sequence characterized amplified region (SCAR) markers SCAR860 and SCAR200. The two SCAR markers were used for detecting F2 segregating population. SCAR860 and SCAR200 existed in resistant plants but were absent in the susceptible plants. We concluded that S2092972 was located on the chromosome 3BL. These markers will be useful for marker-assisted selection and gene pyramiding in wheat resistance breeding.